Supraclavicular flap repair in the free flap era. Issue 6 (17th November 2017) - Trautman, Jodie; Gore, Sinclair; Potter, Matthew; Clark, Jonathan; Hyam, Dylan; Tan, Ngian C.; Ngo, Quan; Ashford, Bruce
Abstract : Background: Supraclavicular flap (SCF) repair is widely reported in head and neck surgery in select patients and defects. The authors' objective is to present our series of 30 patients who underwent SCF repair for varying defects and to review the scope and outcome of SCF repair in the literature. Methods: The authors contributed primary evidence of 30 cases of SCF repair. Our outcomes are compared with those reported in the last 5 years' literature; 33 articles published between January 2012 and January 2017 that present original clinical experience of 528 SCFs. Results: SCF is suitable for a wide variety of oral cavity, pharyngeal, skull base and cutaneous defects. Consistent with our experience, SCF is highly reliable even in previously irradiated or dissected necks, so long as the supraclavicular artery is intact. Our case series shows minor complications in 3/30 (10%) and flap loss in 1/30 (3.3%) cases. The literature reports a similar rate of complete flap failure of 3.4% and a slightly higher average minor complication rate of 24.6%. Conclusion: We add our experience of 30 cases of SCF repair to the international literature. We experienced a complication rate lower than the reported average, and maintain that the SCF is an excellent reconstructive option in patients with previously irradiated necks or comorbidities that affect microvasculature and anaesthetic resilience.